2019
DOI: 10.5539/ies.v12n11p26
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Education: A Missing Link for the Competitive Graduates?

Abstract: The present study is based on the issue of the competitiveness of vocational education graduates. This condition is likely due to the irrelevance between the content or the competencies developed and the superiority of the regions (Regency/Municipality). Therefore, the first step to improve the competitiveness of the graduates is evaluating the accordance of their competencies developed by the vocational education in every region of the regency or municipality. This study used a policy evaluation method formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Overall, though the current study found two factors with "Not Good" category, the rest factor supported the significant result on "Good" category. This carries a meaning that the contents of vocational education reflected in the competence of skills developed (Sukardi, & Fahrurrozi, 2019) can be developed by applying the Good School Governance. The low competitiveness of vocational education graduates, both in entrepreneurship and competitiveness in the national and international labor market can also be increased by Good School Governance.…”
Section: "Good" Categorymentioning
confidence: 99%
“…Overall, though the current study found two factors with "Not Good" category, the rest factor supported the significant result on "Good" category. This carries a meaning that the contents of vocational education reflected in the competence of skills developed (Sukardi, & Fahrurrozi, 2019) can be developed by applying the Good School Governance. The low competitiveness of vocational education graduates, both in entrepreneurship and competitiveness in the national and international labor market can also be increased by Good School Governance.…”
Section: "Good" Categorymentioning
confidence: 99%
“…Therefore, VHS level students are equipped with entrepreneurship skills, both theoretically and practically. It is very essential to strengthen the entrepreneurship aspect, because based on the results of the study by Sukardi et al (2019) found that there was a discrepancy in expertise developed by the Vocational High School (VHS) with the regional issues which became the featured basis. It confirms to be the main reason of the gap between the needs of graduates with the availability of employment (Sala-i-Martín et al, 2015;Wildan & Sukardi, 2011;Sukardi & Wardana, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This situation is influenced by the irrelevance of school competencies with the current state of development of the construction industry technology. The main solution is growing and developing student competitiveness by increasing student competency through vocational education (Rahdiyanta, Nurhadiyanto, & Munadi, 2019), because this condition causes the low competitiveness of competencies in entrepreneurial and technical skills in both national and international markets (Sukardi, Wildan, & Fahrurrozi, 2019;Ismail & Hassan, 2019).…”
Section: Introductionmentioning
confidence: 99%